1990
DOI: 10.1051/rnd:19900403
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ions as a mediator in GnRH action on gonadotropin release in the common carp (Cyprinus carpio L)

Abstract: Summary ― Collagenase-dispersed carp pituitary cells in a perifusion system were used to study the role of calcium ions in the mechanism of GnRH action on the release of maturational gonadotropin (GtH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The enzymatic dispersion of the glands was performed with collagenase H (Boehringer Mannheim, Germany) according to the method of Weil et al (1986) for trout and adapted to carp by Mikolajczyk et al (1990), as described elsewhere (SokolowskaMikolajczyk et al, 2005). After dispersion the cells were resuspended in a pre-incubation medium and transferred into two 96-well microplates (Nunc A/S Denmark), approximately 5 × 10 4 cells in each well.…”
Section: Methodsmentioning
confidence: 99%
“…The enzymatic dispersion of the glands was performed with collagenase H (Boehringer Mannheim, Germany) according to the method of Weil et al (1986) for trout and adapted to carp by Mikolajczyk et al (1990), as described elsewhere (SokolowskaMikolajczyk et al, 2005). After dispersion the cells were resuspended in a pre-incubation medium and transferred into two 96-well microplates (Nunc A/S Denmark), approximately 5 × 10 4 cells in each well.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo experiments in tilapia also showed that GnRHa given at doses higher than 10 pg/kg resulted in a reduced response after 3h (Gissis et al 1991). Diminished response to sGnRH at doses higher than 100 nM was reported in perifused carp pituitary cells (Mikolajczyk et al 1990a). Refractoriness of goldfish pituitary fragments was achieved by prolonged exposure to 100 nM sGnRH, but could be circumvented by Ca 2 + ionophore.…”
Section: Discussionmentioning
confidence: 92%
“…The enzymatic dispersion of the pituitary glands and the technique of cell culture were described in detail elsewhere (Mikolajczyk, Weil, Epler, & Breton, 1990;Sokolowska-Mikolajczyk, Socha, Szczerbik, & Epler, 2009). In brief, collected glands were chopped into small pieces and subjected to dispersion for 6-8 h at 20C in the medium containing 0.1% (w/v) collagenase H (Boehringer Mannheim, Germany) and 1% BSA (Sigma-Aldrich, USA).…”
Section: Culture Techniquementioning
confidence: 99%